Silicon Mitigates the Effects of Calcium, Magnesium, and Sulfur in Plants - da Silva, Dalila Lopes; de Mello Prado, Renato [UNESP] (Springer Nature, 2023)
The role of silicon (Si) as a stress mitigator is already well established, as well as its effects on its relationship with nitrogen (N), phosphorus (P), and potassium (K), but little is known about the relationship of calcium (Ca) and Si in plants. Most studies are focused only on Si, but when it comes to its combined use with Ca, there are very few papers to be found. Si enhances the tolerance to stresses caused by nutritional and water deficiency, salinity, metal toxicity, and heat, in addition to improving photosynthetic activity, increasing enzyme activity, establishing tissue stiffness given the deposition of silica, and promoting an increase in the macronutrients content and micronutrients in plants. Ca is important for plant cultivation, playing a crucial role in cell wall structuring, cell membranes, cell elongation, and signaling. This chapter aims to carry out a brief survey of the effect of the joint supply of Ca and Si in plants, its potential effects in terms of absorption, accumulation, and physiological and structural processes, plus its benefits for men, regarding the biofortification of the edible parts of plants, and their future prospects. We also carried out a brief survey on the relationship of Si with magnesium (Mg) and sulfur (S). However, studies on the interactions of Si with Mg and S are still incipient and further studies are needed.
Keywords: Antioxidant; Ca; Mg; Nutrition deficiency; Physical resistance; Si